Birth Satisfaction Scale/Birth Satisfaction Scale-Revised (BSS/BSS-R): A large scale United States planned home birth and birth centre survey. (October 2016) - Fleming, Susan E.; Donovan-Batson, Colleen; Burduli, Ekaterina; Barbosa-Leiker, Celestina; Hollins Martin, Caroline J.; Martin, Colin R.
Abstract: Objective: to explore the prevalence of birth satisfaction for childbearing women planning to birth in their home or birth centers in the United States. Examining differences in birth satisfaction of the home and birth centers; and those who birthed in a hospital using the 30-item Birth Satisfaction Scale (BSS) and the 10-item Birth Satisfaction Scale-Revised (BSS-R). Study design: a quantitative survey using the BSS and BSS-R were employed. Additional demographic data were collected using electronic linkages (Qualtrics ™ ). Participants: a convenience sample of childbearing women ( n =2229) who had planned to birth in their home or birth center from the US (United States) participated. Participants were recruited via professional and personal contacts, primarily their midwives. Results: the total 30-item BSS score mean was 128.98 (SD 16.92) and the 10-item BSS-R mean score was 31.94 (SD 6.75). Sub-scale mean scores quantified the quality of care provision, women's personal attributes, and stress experienced during labour. Satisfaction was higher for women with vaginal births compared with caesareans deliveries. In addition, satisfaction was higher for women who had both planned to deliver in a home or a birth centre, and who had actually delivered in a home or a birth center. Key conclusions: total and subscale birth satisfaction scores were positive and high for the overall sample Implications for practice: the BSS and the BSS-R provide a robust tool to quantify women's experiences of childbirth between variables such as birth types, birth settings and providers. Highlights: The meaning of birth satisfaction is diverse and may take on many forms. Being respected, in control and listened to, are important constructs of birth satisfaction. Birth satisfaction represents quality of care provision, women's personal attributes and stress experienced during labour.